Effects of n-3 Polyunsaturated Fatty Acids (PUFAs) on Circulating Adiponectin and Leptin in Subjects with Type 2 Diabetes Mellitus - Stirban, A.; Nandrean, S.; Götting, C.; Stratmann, B.; Tschoepe, D. (Hormone and Metabolic Research, 2014)
Recent evidence suggests that omega-3 polyunsaturated fatty acids [n-3 PUFAs: eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)], improve insulin sensitivity in humans. In a double-blind, placebo-controlled, randomized, crossover study, we investigated the effects of EPA/DHA on paraoxonase-1 activity as well as fasting and postprandial levels of circulating adiponectin and leptin in 34 subjects with type 2 diabetes mellitus who received daily for 6 weeks either 2 g purified EPA/DHA or olive oil (placebo), separated by a 6 weeks washout. At the end of each treatment, measurements were performed in fasting state and 2, 4, and 6 h following a standardized high-fat meal (600 kcal). No significant differences in fasting and postprandial circulating adiponectin, leptin, and paraoxonase-1 activity were seen between n-3 PUFAs and placebo. Our data do not support an insulin sensitizing effect of n-3 PUFAs by means of influencing circulating adipocytokines in this population. Clinical Trial Register Number: NCT00328536.
Keywords: diabetes; n-3 polyunsaturated fatty acids; adiponectin; leptin